2009
DOI: 10.1111/j.1460-2466.2008.01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversational Voice, Communicated Commitment, and Public Relations Outcomes in Interactive Online Communication

Abstract: Organizations face unique challenges in communicating interactively online with publics that comprise dauntingly large numbers of individuals. This online survey examined the perceptions of people who had experienced interactive communication with a large consumer-tech-industry company via organizational blogs. Those reporting the greatest exposure to the blogs in this study were more likely to perceive the organization as communicating with a conversational voice. Conversational human voice and communicated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
301
1
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(325 citation statements)
references
References 32 publications
(68 reference statements)
7
301
1
16
Order By: Relevance
“…Against this expectation, however, we observed no unique effects of these variables. Instead, and confirming H4, we observed strong significant effects of Conversational Human Voice (Kelleher, 2009) Although we did not find convincing effects of exposure and Facebook attitude, it seems reasonable to assume that a minimum amount of exposure to-and appreciation of the posts is required. It should be noted that respondents in our study on average indicated to have been exposed to the brand's Facebook posts 10-12 times during this month, and in general positively appreciated the content.…”
Section: Discussioncontrasting
confidence: 34%
See 2 more Smart Citations
“…Against this expectation, however, we observed no unique effects of these variables. Instead, and confirming H4, we observed strong significant effects of Conversational Human Voice (Kelleher, 2009) Although we did not find convincing effects of exposure and Facebook attitude, it seems reasonable to assume that a minimum amount of exposure to-and appreciation of the posts is required. It should be noted that respondents in our study on average indicated to have been exposed to the brand's Facebook posts 10-12 times during this month, and in general positively appreciated the content.…”
Section: Discussioncontrasting
confidence: 34%
“…More than exposure, the perception of an engaging and natural style of communication in the posts (Kelleher, 2009) was associated with changes in brand evaluations. Several other studies have shown that the interactivity that brings about the perception of a conversational human voice is an important driver of positive effects of exposure to brands in social media (e.g., van Noort & Willemsen, 2011;Park & Lee, 2013;Sweetser & Metzgar, 2007;Yang, Kang, & Johnson, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Openness is about openly and freely discussing issues, thoughts and ideas. Assurance is another important feature in the sense that organizations assure their stakeholders that their concerns are legitimate, while also showing they are committed to maintaining the relationships with their stakeholders (Kelleher, 2009;Kelleher, Miller, 2006). Studying the effects of communicated relational commitment in weblogs Kelleher and Miller (2006) found that like the use of this strategy positively affected stakeholders' trust, satisfaction, and commitment (Kelleher, Miller, 2006).…”
Section: Relational Maintenance Strategies To Build and Maintain Relamentioning
confidence: 99%
“…Based on interpersonal communication literature two relational maintenance strategies have been studied regularly: communicated relational commitment and conversational human voice (Kelleher, 2009). Conversational human voice is used by organizations to connect with their stakeholders on a personal level.…”
Section: Relational Maintenance Strategies To Build and Maintain Relamentioning
confidence: 99%